Frontiers of the Lower Palaeolithic expansion in Europe: Tunel Wielki Cave (Poland) - Małgorzata Kot; Claudio Berto; Maciej T. Krajcarz; Magdalena Moskal-del Hoyo; Natalia Gryczewska; Marcin Szymanek; Adrian Marciszak; Krzysztof Stefaniak; Katarzyna Zarzecka-Szubińska; Grzegorz Lipecki; Krzysztof Wertz; Teresa Madeyska (Scientific Reports, 2022)
Abstract Peopling of Central Europe by Middle Pleistocene hominids is highly debatable, mainly due to the relatively harsh climatic and environmental conditions that require cultural and anatomical adjustments. At least several archaeological sites certify human occupation in the region dated back to MIS 13-11, but they represent open-air settlements. Based on the new fieldwork conducted in Tunel Wielki Cave, we can date the human occupation traces in the cave to MIS 14-12. Bipolar-on-anvil knapping technique prevails in the lithic assemblage, made exclusively in flint. The obtained results have given ground for studying the frontiers of human oikumene and the required cultural adaptive abilities.